Fungsi Pengawasan Komisi II DPRD di Bidang Pendidikan (Studi pada DPRD Kota Metro) - S. Endang Prasetyawati (KEADILAN PROGRESIF, 2016)
To achieve the successful implementation of the necessary education in Metro City Metro supervision by the City Council through the Commission II DPRD Metro. The problem in this research is, how to carry out the supervisory function carried out by the Commission II DPRD Metro in education?,. The approach used is normative and empirical. Data obtained from secondary and primary data, qualitative data analysis. The results showed the implementation of the supervisory function carried out by the Commission II DPRD Metro in the field of education is based on the duties, functions and powers attached to the Commission II DPRD Metro that includes preventive and repressive supervision. Suggestions submitted to members of Metro City Council to pay attention to the educational background of Commission II members.